Negative electrode composition, negative electrode for lithium secondary battery comprising the same, lithium secondary battery comprising the negative electrode, and method for preparing the negative electrode composition
Patent Information
- Application Number
- CN202280031910.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2022-01-19
- Filing Date
- 2022-09-30
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2042-09-30
AI Technical Summary
[0007]特别地,随着近来对高密度能量电池的需求增加,已经积极地进行了对使用容量为含石墨材料的容量的10倍以上高的含硅化合物如Si/C或SiOx作为负极活性材料来增加容量的方法进行了研究,但是作为高容量材料的含硅化合物的容量比现有技术中所使用的石墨的容量更高,但是存在的问题在于,在充电过程中体积迅速膨胀而使导电路径断开,导致电池特性劣化
[0037]也就是说,与使用现有的含硅活性材料的情况相比,如本发明那样使用其中所述含硅活性材料被调节至预定粒度范围(公式1和2的范围)的锂二次电池,可以解决在充放电期间使用寿命减少和电阻增加的问题。
Smart Images

Figure CN117256057B_ABST
Abstract
Description
Technical Field
[0001] This application claims priority and benefit to Korean Patent Application No. 10-2021-0131869, filed with the Korean Intellectual Property Office on October 5, 2021, and Korean Patent Application No. 10-2022-0007659, filed with the Korean Intellectual Property Office on January 19, 2022, the entire contents of which are expressly incorporated herein by reference.
[0002] This application relates to a negative electrode composition, a negative electrode for a lithium secondary battery comprising the negative electrode, a lithium secondary battery comprising the negative electrode, and a method for preparing the negative electrode composition. Background Technology
[0003] As the use of fossil fuels increases rapidly, the demand for alternative or clean energy sources is growing. As part of this trend, the most active research area is in the field of power generation and energy storage using electrochemical reactions.
[0004] Currently, representative examples of electrochemical devices using this type of electrochemical energy include secondary batteries, and their applications are expanding.
[0005] With the technological advancements and increasing demands of mobile devices, the need for secondary batteries as an energy source is rapidly growing. Among these secondary batteries, lithium-ion batteries, characterized by high energy density and voltage, long cycle life, and low self-discharge rate, have been commercialized and are widely used. Furthermore, as electrodes for these high-capacity lithium-ion batteries, methods for fabricating high-density electrodes with even higher energy density per unit volume have been actively researched.
[0006] Typically, a secondary battery comprises a positive electrode, a negative electrode, an electrolyte, and a separator. The negative electrode contains a negative electrode active material for inserting and deintercalating lithium ions from the positive electrode; silicon-containing particles with high discharge capacity can be used as the negative electrode active material.
[0007] In particular, with the recent increase in demand for high-density energy batteries, research has been actively conducted on methods to increase capacity by using silicon-containing compounds such as Si / C or SiOx, which have a capacity more than 10 times that of graphite-containing materials, as negative electrode active materials. However, while silicon-containing compounds, as high-capacity materials, have a higher capacity than graphite used in existing technologies, the problem is that their volume expands rapidly during charging, causing the conductive path to break and leading to the degradation of battery characteristics.
[0008] Therefore, in order to solve the problems when using the silicon-containing compound as the negative electrode active material, various measures have been discussed, such as measures to adjust the driving potential, measures to suppress volume expansion itself such as methods to additionally coat the active material layer with a thin film and methods to control the particle size of the silicon-containing compound, or measures to prevent the conductive path from being broken.
[0009] However, due to the poor tortuosity structure caused by the characteristics of silicon-containing active material particles, silicon-containing anodes still exhibit unfavorable characteristics for ion movement. Therefore, it is necessary to study the particle size distribution of the silicon-containing active material itself, which can improve the conductive path.
[0010] [Existing Technical Documents]
[0011] [Patent Literature]
[0012] (Patent Document 1) Japanese Patent Application Publication No. 2009-080971 Summary of the Invention
[0013] Technical issues
[0014] Due to the poor curvature structure caused by the characteristics of silicon-containing active material particles, silicon-containing anodes still exhibit unfavorable ion movement characteristics. As a result of research on improving the conductivity path, it has been found that the fine particles of silicon-containing active materials may hinder ion movement and can also cause the formation of a large amount of solid electrolyte interphase (SEI) layer during charge-discharge cycles through side reactions with the fine particles, leading to a rapid increase in diffusion resistance.
[0015] The present invention has made efforts to provide a negative electrode composition that can solve the above-mentioned problems, a negative electrode for a lithium secondary battery comprising the negative electrode, a lithium secondary battery comprising the negative electrode, and a method for preparing the negative electrode composition.
[0016] Technical solution
[0017] An exemplary embodiment of the present invention provides a negative electrode composition comprising: a silicon-containing active material; a negative electrode conductive material; and a negative electrode binder, wherein the silicon-containing active material comprises silicon-containing particles with a particle size distribution of 0.01 μm or more and 30 μm or less, and relative to 100 parts by weight of the silicon-containing active material, the silicon-containing active material comprises 1 part by weight or more and 5 parts by weight of silicon-containing particles with a particle size of 1 μm or less, and the silicon-containing active material satisfies the particle size ratio of the following formulas 1 and 2:
[0018] [Formula 1]
[0019] 20 ≤ (X1 / Y) × 100 (%)
[0020] [Formula 2]
[0021] (X2 / Y)×100(%)≤230
[0022] In formulas 1 and 2,
[0023] X1 represents the D5 particle size of the silicon-containing active material.
[0024] X2 represents the D95 particle size of the silicon-containing active material, and
[0025] Y represents the median particle size (D50) of the silicon-containing active material.
[0026] Another exemplary embodiment provides a method for preparing a negative electrode composition, the method comprising: forming a mixture by mixing a negative electrode conductive material and a negative electrode binder; performing a first mixing by adding water to the mixture; and performing a second mixing by adding a silicon-containing active material to the mixed mixture, wherein the silicon-containing active material comprises silicon-containing particles with a particle size distribution of 0.01 μm or more and 30 μm or less, and relative to 100 parts by weight of the silicon-containing active material, the silicon-containing active material comprises 1 part by weight or more and 5 parts by weight of silicon-containing particles with a particle size of 1 μm or less, and the silicon-containing active material satisfies the particle size ratio of the following formulas 1 and 2:
[0027] [Formula 1]
[0028] 20 ≤ (X1 / Y) × 100 (%)
[0029] [Formula 2]
[0030] (X2 / Y)×100(%)≤230
[0031] Another exemplary embodiment provides a negative electrode for a lithium secondary battery, comprising: a negative electrode current collector layer; and a negative electrode active material layer formed on one or both surfaces of the negative electrode current collector layer, the negative electrode active material layer comprising a negative electrode composition according to the present application.
[0032] Another exemplary embodiment provides a lithium secondary battery, comprising: a positive electrode; a negative electrode for a lithium secondary battery according to the present application; a separator disposed between the positive electrode and the negative electrode; and an electrolyte.
[0033] Beneficial effects
[0034] In the case of anodes using existing silicon-containing active materials, especially anodes using pure Si particles, there is a characteristic of being able to manufacture high-capacity and high-density batteries. However, the higher the purity of the Si particles, the more problems arise due to volume expansion. Therefore, this problem is solved by including oxides such as SiO. However, this still has the characteristic of being unfavorable to ion movement due to poor curvature structure. In the case of the anode composition according to this application, the main object of the present invention is to solve this problem by using a silicon-containing active material in which the micronization of silicon-containing particles is controlled and meets a specific particle size range.
[0035] The negative electrode composition according to an exemplary embodiment of the present invention is characterized in that, when using a silicon-containing active material as a high-capacity material for manufacturing a high-capacity battery, the properties of the silicon-containing active material itself are modified, rather than adjusting the properties of the conductive material and the binder based on the volume expansion of the silicon-containing active material. Specifically, the silicon-containing active material is characterized in that it comprises silicon-containing particles with a particle size distribution of 0.01 μm or more and 30 μm or less, and the content of silicon-containing particles with a particle size of 1 μm or less is 1 part by weight or more and 5 parts by weight or less relative to 100 parts by weight of the silicon-containing active material, and the particle size distribution of the silicon-containing active material is adjusted to the range of Formulas 1 and 2.
[0036] In other words, the advantages of the negative electrode composition according to this application are as follows: from the viewpoint of the curvature within the electrode, the removal of fine particles by including a silicon-containing active material with a particle size distribution controlled as described above is advantageous for the movement of lithium ions (conductive path) during charging and discharging. Furthermore, while fine silicon particles that may hinder lithium ion movement during charging and discharging can cause side reactions by reacting with lithium ions, inducing an increase in diffusion resistance, by including a silicon-containing active material whose particle size distribution is controlled within the range of Formulas 1 and 2 of this application, the rate of increase in diffusion resistance can be significantly controlled even if the charging and discharging process continues to cycle.
[0037] In other words, compared with the use of existing silicon-containing active materials, lithium secondary batteries using the silicon-containing active materials of the present invention, which are adjusted to a predetermined particle size range (the range of Formulas 1 and 2), can solve the problems of reduced lifespan and increased resistance during charge and discharge. Attached Figure Description
[0038] Figure 1 This is a view showing a stacked structure of a negative electrode for a lithium secondary battery according to an exemplary embodiment of this application.
[0039] Figure 2 This is a view showing a stacked structure of a negative electrode for a lithium secondary battery according to an exemplary embodiment of this application.
[0040] Figure 3 This is a view showing the stacked structure of a lithium secondary battery according to an exemplary embodiment of this application.
[0041] <Explanation of Figure Markers>
[0042] 10: Negative electrode current collector layer
[0043] 20: Negative electrode active material layer
[0044] 30: Diaphragm
[0045] 40: Positive electrode active material layer
[0046] 50: Positive current collector layer
[0047] 100: Negative electrode for lithium secondary batteries
[0048] 200: Positive electrode for lithium secondary batteries Detailed Implementation
[0049] Before describing the present invention, some terms will be defined.
[0050] In this specification, unless otherwise specifically stated, when a part “contains” a constituent element, it does not mean that another constituent element is excluded, but rather that another constituent element may be further contained.
[0051] In this specification, "p to q" refers to the range of "p and below q".
[0052] In this specification, "specific surface area" is measured by the BET method, specifically using a BELSORP-mino II manufactured by BEL Japan, Inc., calculated from the amount of nitrogen adsorbed at liquid nitrogen temperature (77K). In other words, in this application, BET specific surface area can refer to the specific surface area measured by the aforementioned method.
[0053] In this specification, "Dn" refers to the particle size distribution, specifically the particle size at the n% point of the cumulative particle number distribution based on particle size. That is, D50 is the particle size (median particle size) at the 50% point of the cumulative particle number distribution based on particle size, D90 is the particle size at the 90% point of the cumulative particle number distribution based on particle size, and D10 is the particle size at the 10% point of the cumulative particle number distribution based on particle size. Furthermore, D95 is the particle size at the 95% point of the cumulative particle number distribution based on particle size, and D5 is the particle size at the 5% point of the cumulative particle number distribution based on particle size. Alternatively, the median particle size can be measured using laser diffraction. Specifically, after dispersing the powder to be tested in a dispersion medium, the resulting dispersion is introduced into a commercially available laser diffraction particle size measurement device (e.g., Microtrac S3500), and the particle size distribution is calculated by measuring the difference in the diffraction pattern as the particles pass through the laser beam.
[0054] In one exemplary embodiment of this application, the particle size or particle diameter may refer to the average or representative diameter of the individual particles forming the powder.
[0055] In this specification, the fact that a polymer contains monomers as monomeric units means that the monomers participate in the polymerization reaction and are therefore included in the polymer as repeating units. In this specification, when a polymer contains monomers, it is interpreted in the same way as when the polymer contains monomers as monomeric units.
[0056] In this specification, "polymer" is understood to be used in a broad sense and includes copolymers unless otherwise stated as "homogeneous polymer".
[0057] In this specification, weight-average molecular weight (Mw) and number-average molecular weight (Mn) are converted molecular weights of polystyrene measured by gel permeation chromatography (GPC) using commercially available monodisperse polystyrene polymers (standard samples) with various degrees of polymerization as standard materials. Unless otherwise stated, molecular weight in this specification refers to weight-average molecular weight.
[0058] The present invention will now be described in detail with reference to the accompanying drawings, enabling those skilled in the art to readily implement it. However, the present invention can be implemented in various different forms and is not limited to the following description.
[0059] An exemplary embodiment of this specification provides a negative electrode composition comprising: a silicon-containing active material; a negative electrode conductive material; and a negative electrode binder, wherein the silicon-containing active material comprises silicon-containing particles with a particle size distribution of 0.01 μm or more and 30 μm or less, and comprises, relative to 100 parts by weight, 1 part by weight or more and 5 parts by weight of silicon-containing particles with a particle size of 1 μm or less, and the silicon-containing active material satisfies the particle size ratios of Formulas 1 and 2.
[0060] A negative electrode composition according to an exemplary embodiment of the present invention is characterized in that when a silicon-containing active material as a high-capacity material is used for manufacturing a high-capacity battery, the properties of the silicon-containing active material itself are modified, instead of adjusting the properties of the conductive material and the binder according to the volume expansion of the silicon-containing active material. Specifically, the present invention is characterized by comprising silicon-containing particles having a particle size distribution of 0.01 μm or more and 30 μm or less, wherein the content of the silicon-containing particles having a particle size of 1 μm or less is 1 part by weight or more and 5 parts by weight or less relative to 100 parts by weight of the silicon-containing active material, and the particle size distribution of the silicon-containing active material is adjusted to the ranges of Formula 1 and Formula 2.
[0061] In an exemplary embodiment of the present application, in a negative electrode composition comprising a silicon-containing active material, a negative electrode conductive material and a negative electrode binder, the silicon-containing active material comprises silicon-containing particles having a particle size distribution of 0.01 μm or more and 30 μm or less, and comprises 1 part by weight or more and 5 parts by weight or less of silicon-containing particles having a particle size of 1 μm or less relative to 100 parts by weight of the silicon-containing active material, the D5 / D50 ratio of the silicon-containing active material may be 20% or more, and the D95 / D50 ratio of the silicon-containing active material may be 230% or less.
[0062] In an exemplary embodiment of the present application, the Dx / Dy ratio of the silicon-containing active material may be calculated by a general calculation method for ratios, and the calculation formula may be expressed as (Dx / Dy)×100 (%). That is, as an example, the D95 / D50 ratio of the silicon-containing active material may be calculated as (D95 / D50)×100.
[0063] In an exemplary embodiment of the present application, there is provided a negative electrode composition, wherein the silicon-containing particles comprise one or more selected from the group consisting of SiOₓ (x=0), SiOₓ (0<x<2), SiC and Si alloys.
[0064] In an exemplary embodiment of the present application, there is provided a negative electrode composition, wherein the silicon-containing particles comprise one or more selected from SiOₓ (x=0) and SiOₓ (0<x<2), and comprise 70 parts by weight or more of the SiOₓ (x=0) relative to 100 parts by weight of the silicon-containing active material.
[0065] In an exemplary embodiment of the present application, there is provided a negative electrode composition, wherein the silicon-containing particles comprise SiOₓ (x=0), and comprise 70 parts by weight or more of the SiOₓ (x=0) relative to 100 parts by weight of the silicon-containing active material.
[0066] In another exemplary embodiment, the content of SiOx (x=0) relative to 100 parts by weight of silicon-containing active material can be 70 parts by weight or more, preferably 80 parts by weight or more, more preferably 90 parts by weight or more, and the content can be 100 parts by weight or less, preferably 99 parts by weight or less, more preferably 95 parts by weight or less.
[0067] In one exemplary embodiment of this application, the silicon-containing active material, which specifically comprises pure silicon (Si) particles, can be used as the silicon-containing active material. Using pure silicon (Si) particles as the silicon-containing active material means that, relative to the total 100 parts by weight of the silicon-containing active material as described above, the pure Si particles (SiOx (x=0)) contained therein that are not bound to other particles or elements are within the range described above.
[0068] In one exemplary embodiment of this application, the silicon-containing active material may be composed of silicon-containing particles having 100 parts by weight of SiOx (x=0) relative to 100 parts by weight of the silicon-containing active material.
[0069] In one exemplary embodiment of this application, the silicon-containing active material may contain metallic impurities. In this case, the impurities are metals that are typically present in the silicon-containing active material, specifically, the content may be less than 0.1 parts by weight relative to 100 parts by weight of the silicon-containing active material.
[0070] Because silicon-containing active materials have significantly higher capacity compared to graphite-containing active materials used in the prior art, attempts to apply silicon-containing active materials are increasing. However, due to the high volume expansion rate of silicon-containing active materials during charge and discharge, these attempts are limited to situations such as the use of small amounts of silicon-containing active materials mixed with graphite-containing active materials.
[0071] Therefore, while using only the silicon-containing active material as the negative electrode active material to improve capacity performance, and in order to solve problems such as electrode curvature and increased diffusion resistance caused by charge-discharge cycles, the present invention addresses existing problems by adjusting the particle size distribution of the silicon-containing active material itself rather than adjusting the composition of the conductive material and the binder.
[0072] In one exemplary embodiment of this application, the silicon-containing active material may comprise silicon-containing particles with a particle size distribution of 0.01 μm or more and 30 μm or less.
[0073] The fact that the silicon-containing active material contains silicon-containing particles with a particle size distribution of 0.01 μm or larger and 30 μm or smaller means that it contains a large number of individual silicon-containing particles with a particle size within the above range, and the number of silicon-containing particles contained is not limited.
[0074] When the silicon-containing particles have a spherical shape, the particle size of the silicon-containing particles can be expressed as the diameter of the silicon-containing particles. However, even in the case of other non-spherical shapes, the particle size can be measured by comparison with the spherical case. Generally speaking, the particle size of a single silicon-containing particle can be measured by measurement methods in the art.
[0075] In one exemplary embodiment of this application, the content of silicon-containing particles with a particle size of less than 1 μm can be more than 1 part by weight and less than 5 parts by weight relative to 100 parts by weight of silicon-containing active material.
[0076] In another exemplary embodiment, the content of silicon-containing particles with a particle size of less than 1 μm can be more than 1 part by weight and less than 5 parts by weight, preferably more than 1 part by weight and less than 4 parts by weight, and more than 1.2 parts by weight and less than 4 parts by weight, relative to 100 parts by weight of silicon-containing active material.
[0077] In other words, the silicon-containing active material according to the present invention has silicon-containing particles with a particle size distribution of 0.01 μm or more and 30 μm or less, and also has silicon-containing particles with a particle size of 1 μm or less within the above range, and can be represented as a silicon-containing active material in which the micronization of silicon-containing particles is controlled.
[0078] Since the silicon-containing active material according to the present invention meets the above-mentioned weight range, fine silicon-containing particles can be removed to form a structure that is advantageous in terms of curvature within the electrode, thereby preventing an increase in diffusion resistance, and the rate of increase in diffusion resistance can be significantly controlled even if the charge-discharge cycle continues. This is a result of controlling the small-particle silicon-containing active material that undergoes side reactions with lithium ions, and has the characteristic of increasing the lifespan and capacity of the electrode containing the silicon-containing active material.
[0079] In one exemplary embodiment of this application, a negative electrode composition is provided, wherein the D5 / D50 ratio of the silicon-containing active material is 20% or more, and the D95 / D50 ratio of the silicon-containing active material is 230% or less.
[0080] The above formula can be applied to the D5 / D50 ratio and the D95 / D50 ratio. Specifically, the formula can be applied as (D5 / D50)×100(%) and (D95 / D50)×100(%).
[0081] In one exemplary embodiment of this application, the D5 / D50 ratio of the silicon-containing active material can be expressed as Formula 1.
[0082] In one exemplary embodiment of this application, Formula 1 can satisfy 20 ≤ (X1 / Y) × 100 (%).
[0083] In another exemplary embodiment, Formula 1 can be 20≤(X1 / Y)×100(%), preferably 25≤(X1 / Y)×100(%), more preferably 30≤(X1 / Y)×100(%), which can satisfy the range of (X1 / Y)×100(%)≤80, preferably (X1 / Y)×100(%)≤70, and more preferably (X1 / Y)×100(%)≤55.
[0084] In one exemplary embodiment of this application, the D5 / D50 ratio of the silicon-containing active material can be 20% or more, preferably 25% or more, more preferably 30% or more, and can satisfy the range of 80% or less, preferably 70% or less, more preferably 55% or less.
[0085] In one exemplary embodiment of this application, the D95 / D50 ratio of the silicon-containing active material can be expressed as Formula 2.
[0086] In one exemplary embodiment of this application, Formula 2 can satisfy (X2 / Y)×100(%)≤230.
[0087] In one exemplary embodiment of this application, the D95 / D50 ratio of the silicon-containing active material can be in the range of less than 230%, preferably less than 220%, most preferably less than 210%, and can be in the range of more than 180%, preferably more than 190%.
[0088] In one exemplary embodiment of this application, Formula 2 can satisfy the range of (X2 / Y)×100(%)≤230, preferably (X2 / Y)×100(%)≤220, more preferably (X2 / Y)×100(%)≤210, and can satisfy the range of 180≤(X2 / Y)×100(%), preferably 190≤(X2 / Y)×100(%).
[0089] Since the D5 / D50 ratio (Formula 1) and D95 / D50 ratio (Formula 2) of the silicon-containing active material according to this application are adjusted to the above range, the present invention has the feature that an advantageous structure in terms of the curvature within the electrode can be formed, and the rate at which the diffusion resistance increases with the continuation of charge-discharge cycles can also be controlled.
[0090] In one exemplary embodiment of this application, Y represents the median particle size (D50) of the silicon-containing active material. Specifically, Y can satisfy the range of 3 μm or more and 10 μm or less, preferably 4 μm or more and 7 μm or less, and more preferably 4.5 μm or more and 7 μm or less.
[0091] In one exemplary embodiment of this application, X1 represents the D5 particle size of the silicon-containing active material. Specifically, X1 can be in the range of 2 μm or more and 5 μm or less, preferably 2.3 μm or more and 4 μm or less, and more preferably 2.5 μm or more and 4 μm or less.
[0092] In one exemplary embodiment of this application, X2 represents the D95 particle size of the silicon-containing active material. Specifically, X2 can be in the range of 6 μm or more and 15 μm or less, preferably 7 μm or more and 14 μm or less, and more preferably 8 μm or more and 14 μm or less.
[0093] In one exemplary embodiment of this application, a negative electrode composition is provided, wherein the D5 / D95 ratio of the silicon-containing active material is 20% or more.
[0094] The above formula can be applied to the D5 / D95 ratio. Specifically, the formula can be applied as (D5 / D95)×100 (%).
[0095] In other words, in one exemplary embodiment of this application, a negative electrode composition is provided, wherein the silicon-containing active material satisfies the particle size ratio of the following formula 3:
[0096] [Formula 3]
[0097] 10 ≤ (X1 / X2) × 100 (%)
[0098] In formula 3,
[0099] X1 represents the D5 particle size of the silicon-containing active material, and
[0100] X2 represents the D95 particle size of the silicon-containing active material.
[0101] In another exemplary embodiment, Formula 3 can satisfy the range of 10≤(X1 / X2)×100(%), preferably 15≤(X1 / X2)×100(%), more preferably 20≤(X1 / X2)×100(%), and can satisfy the range of (X1 / X2)×100(%)≤70, preferably (X1 / X2)×100(%)≤60, more preferably (X1 / X2)×100(%)≤55.
[0102] In one exemplary embodiment of this application, a negative electrode composition is provided, wherein the silicon-containing particles with a particle size distribution of 0.01 μm or more and 30 μm or less have a full width at half maximum (FWHM) of 1 μm or more and 5 μm or less.
[0103] The fact that the D5 / D95 ratio (Formula 3) and the full width at half maximum (FWHM) ratio are satisfied means that a sharp particle size distribution is formed in the particle size distribution (PSD) diagram. Since the above range is satisfied, even when using silicon-containing active materials containing pure Si, the present invention still has the feature of being able to solve the problem of increased resistance by suppressing the side reactions caused by charging and discharging.
[0104] The particle size distribution (PSD) is a numerical list or mathematical function that defines the relative amount of particles present based on size. It can provide information about the width of the particle size span, and D10, D50, and D90 (known as D values or three-point specifications) are the most widely used values in PSD analysis. These values represent the particle size at 10%, 50%, and 90% of the cumulative distribution.
[0105] For example, assuming D50 is 100 nm, it means that 50% of the particles in the sample are larger than 100 nm and 50% are smaller than 100 nm. Other parameters related to size distribution can be calculated using D10, D50, and D90. For example, span—an indicator of distribution width—can be calculated as follows:
[0106] Span = (D90 - D10) / D50.
[0107] In one exemplary embodiment of this application, the Dmax of the silicon-containing active material can be in the range of less than 30 μm. Specifically, the Dmax can be in the range of less than 30 μm and less than 27 μm, and can be greater than 10 μm.
[0108] In one exemplary embodiment of this application, the Dmin of the silicon-containing active material can be in the range of 0.5 μm or more. Specifically, the Dmin can be in the range of 0.5 μm or more, 1 μm or more, and below 5 μm.
[0109] Dmax and Dmin can refer to the particle size of the silicon-containing active material containing silicon particles, with the largest particle size (Dmax) and the smallest particle size (Dmin).
[0110] In one exemplary embodiment of this application, the silicon-containing active material typically has a characteristic BET specific surface area. The preferred BET specific surface area of the silicon-containing active material is 0.01 m². 2 / g to 150.0m 2 / g, more preferably 0.1m 2 / g to 100.0m 2 / g, particularly preferably 0.2m 2 / g to 80.0m 2 / g, the optimal value is 0.2m2 / g to 18.0m 2 / g. The BET specific surface area was measured using DIN 66131 (using nitrogen).
[0111] In one exemplary embodiment of this application, the silicon-containing active material may exist, for example, in a crystalline or amorphous form, and is preferably not porous. The silicon particles are preferably spherical or fragmented particles. Alternatively, but less preferably, the silicon particles may also have a fibrous structure, or exist in the form of a silicon-containing film or coating.
[0112] In one exemplary embodiment of this application, a negative electrode composition is provided, wherein the amount of the silicon-containing active material present is 60 parts by weight or more relative to 100 parts by weight of the negative electrode composition.
[0113] In another exemplary embodiment, the amount of the silicon-containing active material present relative to 100 parts by weight of the negative electrode composition may be 60 parts by weight or more, preferably 65 parts by weight or more, more preferably 70 parts by weight or more, and the amount present may be 95 parts by weight or less, preferably 90 parts by weight or less, more preferably 80 parts by weight or less.
[0114] The negative electrode composition according to this application is characterized in that, when a silicon-containing active material with significantly high capacity is used within the above-mentioned range, the problems of increased resistance and reduced service life can be solved by adjusting the particle size of the silicon-containing active material itself.
[0115] In one exemplary embodiment of this application, the silicon-containing active material may have a non-spherical shape with a sphericity of, for example, less than 0.9, such as 0.7 to 0.9, such as 0.8 to 0.9, such as 0.85 to 0.9.
[0116] In this application, the sphericity is determined by the following formula A-1, where A is the area and P is the boundary line.
[0117] [Formula A-1]
[0118] 4πA / P 2
[0119] In existing technologies, graphite-containing compounds are typically used as negative electrode active materials. However, recently, with the increasing demand for high-capacity batteries, attempts to mix and use silicon-containing active materials are increasing to increase capacity. However, in the case of silicon-containing active materials, even if the properties of the silicon-containing active material itself are adjusted as described above, the volume expands rapidly during charging and discharging, which may lead to damage to the conductive paths formed in the negative electrode active material layer in some cases.
[0120] Therefore, in one exemplary embodiment of this application, the negative electrode conductive material may comprise one or more of the following: point conductive material, surface conductive material, and line conductive material.
[0121] In one exemplary embodiment of this application, the dot-shaped conductive material can be used to enhance the conductivity of the negative electrode, and refers to a spherical or dot-shaped conductive material that is conductive and does not induce chemical changes. Specifically, the dot-shaped conductive material can be selected from at least one of the following: natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal cracking black, conductive fibers, fluorocarbons, aluminum powder, nickel powder, zinc oxide, potassium titanate, titanium oxide, and polyphenylene derivatives, and preferably includes carbon black for achieving high conductivity and excellent dispersibility.
[0122] In one exemplary embodiment of this application, the BET specific surface area of the dot-shaped conductive material can be 40m². 2 / g or more and 70m 2 / g or less, preferably 45m 2 / g or more and 65m 2 / g or less, preferably 50m 2 / g or more and 60m 2 / g or less.
[0123] In one exemplary embodiment of this application, the functional group content (volatile matter) of the dot-shaped conductive material can be 0.01% or more and 1% or less, preferably 0.01% or more and 0.3% or less, and more preferably 0.01% or more and 0.1% or less.
[0124] In particular, when the functional group content of the dot-shaped conductive material meets the above-mentioned range, functional groups exist on the surface of the dot-shaped conductive material, so that when water is used as a solvent, the dot-shaped conductive material can be smoothly dispersed in the solvent.
[0125] In one exemplary embodiment of this application, the silicon-containing active material is characterized by comprising a dot-shaped conductive material having a functional group content within the aforementioned range, wherein the functional group content can be adjusted according to the degree of heat treatment of the dot-shaped conductive material.
[0126] In other words, in the manufacturing of the dot-shaped conductive material, a high functional group content means the presence of a large number of foreign objects, while a low functional group content may mean that more frequent heat treatment processing has been performed.
[0127] In one exemplary embodiment of this application, the particle size of the dot-shaped conductive material can be from 10 nm to 100 nm, preferably from 20 nm to 90 nm, and more preferably from 20 nm to 60 nm.
[0128] In one exemplary embodiment of this application, the conductive material may comprise a planar conductive material.
[0129] The planar conductive material can increase the surface contact between silicon particles in the negative electrode to improve conductivity, while suppressing the breakage of the conductive path caused by volume expansion, and can be represented as a plate-shaped conductive material or a block-shaped conductive material.
[0130] In one exemplary embodiment of this application, the planar conductive material may comprise at least one selected from plate graphite, graphene, graphene oxide, and graphite flakes, and may preferably be plate graphite.
[0131] In one exemplary embodiment of this application, the average particle size (D50) of the planar conductive material can be from 2 μm to 7 μm, specifically from 3 μm to 6 μm, and more specifically from 4 μm to 5 μm. When the average particle size meets the above range, sufficient particle size promotes dispersion without causing an excessive increase in the viscosity of the negative electrode slurry. Therefore, when dispersing particles using the same equipment and time, the dispersion effect is excellent.
[0132] In one exemplary embodiment of this application, a negative electrode composition is provided, wherein the planar conductive material has a D10 of 0.5 μm or more and 1.5 μm or less, a D50 of 2.5 μm or more and 3.5 μm or less, and a D90 of 7.0 μm or more and 15.0 μm or less.
[0133] In one exemplary embodiment of this application, a high specific surface area planar conductive material with a high BET specific surface area or a low specific surface area planar conductive material can be used as the planar conductive material.
[0134] In one exemplary embodiment of this application, high specific surface area planar conductive materials or low specific surface area planar conductive materials can be used as the planar conductive material without limitation. However, since the electrode performance can be affected to some extent by the dispersion effect, it may be particularly desirable to use a low specific surface area planar conductive material that will not cause dispersion problems as the planar conductive material according to this application.
[0135] In one exemplary embodiment of this application, the BET specific surface area of the planar conductive material can be 5m². 2 / g or more.
[0136] In another exemplary embodiment, the BET specific surface area of the planar conductive material can be 5m². 2 / g or more and 500m 2 / g or less, preferably 5m 2 / g or more and 300m 2 / g or less, preferably 5m 2 / g or more and 250m 2 / g or less.
[0137] In yet another exemplary embodiment, the planar conductive material is a high specific surface area planar conductive material, and the BET specific surface area can meet 50m². 2 / g or more and 500m 2 / g or less, preferably 80m 2 / g or more and 300m 2 / g or less, more preferably 100m 2 / g or more and 300m 2 The range below / g.
[0138] In another exemplary embodiment, the planar conductive material is a planar conductive material with a low specific surface area, and the BET specific surface area can meet the requirement of 5m². 2 / g or more and 40m 2 / g or less, preferably 5m 2 / g or more and 30m 2 / g or less, preferably 5m 2 / g or more and 25m 2 The range below / g.
[0139] Other conductive materials include linear conductive materials such as carbon nanotubes. The carbon nanotubes can be bundled carbon nanotubes. A bundled carbon nanotube can comprise multiple carbon nanotube units. Specifically, unless otherwise stated, the term "bundled" as used herein refers to a secondary shape in the form of a bundle or rope, wherein multiple carbon nanotube units are arranged side-by-side or entangled together with a orientation substantially the same as the longitudinal axis of the carbon nanotube units. Within the carbon nanotube units, the graphite sheets have a cylindrical shape with nanometer-scale diameters and an sp2 bond structure. In this case, the carbon nanotube units can exhibit conductive or semiconductor properties depending on the angle and structure of the graphite sheets being rolled up. Compared to entangled carbon nanotubes, bundled carbon nanotubes can be uniformly dispersed during anode fabrication and can improve the conductivity of the anode by smoothly forming a conductive network within it.
[0140] In one exemplary embodiment of this application, the linear conductive material may comprise single-walled carbon nanotubes (SWCNTs) or multi-walled carbon nanotubes (MWCNTs).
[0141] In one exemplary embodiment of this application, a negative electrode composition is provided, wherein the content of the negative electrode conductive material is 10 parts by weight or more and 40 parts by weight or less relative to 100 parts by weight of the negative electrode composition.
[0142] In another exemplary embodiment, the content of the negative electrode conductive material relative to 100 parts by weight of the negative electrode composition may be 10 parts by weight or more and 40 parts by weight or less, preferably 10 parts by weight or more and 30 parts by weight or less, and more preferably 15 parts by weight or more and 25 parts by weight or less.
[0143] In one exemplary embodiment of this application, a negative electrode composition is provided, wherein the negative electrode conductive material comprises a planar conductive material and a linear conductive material.
[0144] In one exemplary embodiment of this application, the negative electrode conductive material comprises a planar conductive material and a linear conductive material, and relative to 100 parts by weight of the negative electrode conductive material, it may comprise 0.01 parts by weight and 10 parts by weight of the linear conductive material; and 90 parts by weight and 99.99 parts by weight of the planar conductive material.
[0145] In another exemplary embodiment, the content of the linear conductive material may be 0.01 parts by weight or more and 10 parts by weight or less relative to 100 parts by weight of the negative electrode conductive material, preferably 0.05 parts by weight or more and 5 parts by weight or less, and more preferably 0.1 parts by weight or more and 3 parts by weight or less.
[0146] In yet another exemplary embodiment, the content of the planar conductive material relative to 100 parts by weight of the negative electrode conductive material can be 90 parts by weight or more and 99.99 parts by weight or less, preferably 95 parts by weight or more and 99.95 parts by weight or less, and more preferably 97 parts by weight or more and 99.99 parts by weight or less.
[0147] In particular, in an exemplary embodiment of this application, since the negative electrode conductive material comprises planar conductive material and linear conductive material and each satisfies the composition and ratio, the negative electrode conductive material is characterized by: having no significant impact on the lifespan characteristics of existing lithium secondary batteries, and increasing the number of charge and discharge points of the battery, thereby achieving excellent output characteristics at high C-rates.
[0148] The negative electrode conductive material according to this application has a completely different structure from the positive electrode conductive material applied to the positive electrode. That is, the negative electrode conductive material according to this application is used to capture the contact points between silicon-containing active materials where the volume expansion of the electrode due to charging and discharging is very large, while the positive electrode conductive material is used as a buffer during rolling and also imparts partial conductivity. Its structure and function are completely different from the negative electrode conductive material of this invention.
[0149] The negative electrode conductive material according to this application is applied to the silicon-containing active material and has a completely different structure from the conductive material applied to the graphite-containing active material. That is, the conductive material used for the electrode having the graphite-containing active material has only small particles relative to the active material, thereby having the properties of enhancing output characteristics and imparting partial conductivity. Its structure and function are completely different from the negative electrode conductive material used together with the silicon-containing active material in this invention.
[0150] In one exemplary embodiment of this application, the planar conductive material used as the aforementioned negative electrode conductive material has a different structure and function than the carbon-containing active material commonly used as an existing negative electrode active material. Specifically, the carbon-containing active material used as the negative electrode active material can be artificial graphite or natural graphite, and refers to a material that has been processed into spherical or dot-shaped forms and used to promote the storage and release of lithium ions.
[0151] Conversely, planar conductive materials used as negative electrode conductive materials are materials with planar or plate-like shapes, and can be represented as plate-like graphite. That is, the planar conductive material is a material included to maintain the conductive path in the negative electrode active material layer, and refers to a material that ensures the conductive path in a planar form within the negative electrode active material layer rather than serving to store and release lithium.
[0152] In other words, in this application, the use of plate-shaped graphite as a conductive material means that the plate-shaped graphite is processed into a planar or plate-like shape and serves as a material to ensure a conductive path rather than to store or release lithium. In this case, the included negative electrode active material has high capacity characteristics for lithium storage and release, and serves to store and release all lithium ions transferred from the positive electrode.
[0153] Conversely, in this application, the fact that carbon-containing active materials are used as active materials means that the carbon-containing active materials are processed into dots or spheres and used as materials that store or release lithium.
[0154] In other words, in one exemplary embodiment of this application, the artificial or natural graphite used as a carbon-containing active material is dot-shaped, and its BET specific surface area can meet the requirement of 0.1 m². 2 / g or more and 4.5m 2 The range is below / g. Furthermore, the plate-shaped graphite, as a planar conductive material, is planar, and its BET specific surface area can be 5m². 2 / g or more.
[0155] In one exemplary embodiment of this application, the negative electrode binder of the negative electrode composition may contain at least one of the following: polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidene fluoride, polyacrylonitrile, polymethyl methacrylate, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, polyacrylic acid, ethylene-propylene-diene monomer (EPDM), sulfonated EPDM, styrene-butadiene rubber (SBR), fluororubber, polyacrylic acid, and materials in which hydrogen is replaced by Li, Na, Ca, etc., and may also contain various polymers thereof.
[0156] According to an exemplary embodiment of this application, the negative electrode adhesive serves to support the active material and the conductive material to prevent distortion and structural deformation of the negative electrode structure during the volume expansion and relaxation of the silicon-containing active material. When the above function is satisfied, all conventional adhesives can be applied. Specifically, water-based adhesives can be used, and more specifically, polyacrylamide (PAM) based adhesives can be used.
[0157] In one exemplary embodiment of this application, the content of the negative electrode adhesive relative to 100 parts by weight of the negative electrode composition may be 30 parts by weight or less, preferably 25 parts by weight or less, more preferably 20 parts by weight or less, and the content may be 5 parts by weight or more and 10 parts by weight or more.
[0158] In one exemplary embodiment of this application, a method for preparing a negative electrode composition is provided, the method comprising: forming a mixture by mixing a negative electrode conductive material and a negative electrode binder; performing a first mixing by adding water to the mixture; and performing a second mixing by adding a silicon-containing active material to the mixed mixture, wherein the silicon-containing active material comprises silicon-containing particles with a particle size distribution of 0.01 μm or more and 30 μm or less, and comprises, relative to 100 parts by weight, 1 part by weight and 5 parts by weight of the silicon-containing active material, wherein the silicon-containing active material satisfies the particle size ratio of the following formulas 1 and 2:
[0159] [Formula 1]
[0160] 20 ≤ (X1 / Y) × 100 (%)
[0161] [Formula 2]
[0162] (X2 / Y)×100(%)≤230
[0163] In formulas 1 and 2,
[0164] X1 represents the D5 particle size of the silicon-containing active material.
[0165] X2 represents the D95 particle size of the silicon-containing active material, and
[0166] Y represents the median particle size (D50) of the silicon-containing active material.
[0167] In another exemplary embodiment, a method for preparing a negative electrode composition is provided, the method comprising: forming a mixture by mixing a negative electrode conductive material and a negative electrode binder; performing a first mixing by adding water to the mixture; and performing a second mixing by adding a silicon-containing active material to the mixed mixture, wherein the silicon-containing active material comprises silicon-containing particles with a particle size distribution of 0.01 μm or more and 30 μm or less, and comprises, relative to 100 parts by weight, 1 part by weight and 5 parts by weight of the silicon-containing active material, the silicon-containing active material having a D5 / D50 ratio of 20% or more, and the silicon-containing active material having a D95 / D50 ratio of 230% or less.
[0168] In the preparation method of the negative electrode composition, the components contained in the negative electrode composition can be the same as those described above.
[0169] In one exemplary embodiment of this application, a method for preparing a negative electrode composition is provided, wherein in the first mixing and second mixing steps, mixing is performed at 2,000 rpm to 3,000 rpm for 10 minutes to 60 minutes.
[0170] In one exemplary embodiment of this application, a negative electrode for a lithium secondary battery is provided, comprising: a negative electrode current collector layer; and a negative electrode active material layer formed on one or both surfaces of the negative electrode current collector layer, the negative electrode active material layer comprising a negative electrode composition according to this application.
[0171] Figure 1 This is a view illustrating the stacked structure of a negative electrode for a lithium secondary battery according to an exemplary embodiment of this application. Specifically, it can be confirmed that the negative electrode 100 for a lithium secondary battery includes a negative electrode active material layer 20 on one surface of the negative electrode current collector layer 10. Figure 1 A layer of negative electrode active material formed on one surface is shown. In another embodiment, the negative electrode active material layer may also be contained on both surfaces of the negative electrode current collector layer.
[0172] Specifically, Figure 2This is a view illustrating the stacked structure of a negative electrode for a lithium secondary battery according to an exemplary embodiment of this application. As described above, negative electrode active material layers are included on both sides of the negative electrode current collector layer 10, confirming that the negative electrode 100 for a lithium secondary battery includes negative electrode active material layers 20 on both sides of the negative electrode current collector layer 10. Figure 1 The single-sided coating shown is actually quite rare, and can be as follows: Figure 2 The diagram shows active material layers coated on both sides of the current collector layer. In this case, a negative electrode can be manufactured if the negative electrode composition of the present invention is contained on at least one surface of the current collector layer. That is, the compositions of the active material layers coated on both sides can be the same or different from each other. When the compositions are different, commonly used active material layers such as carbon-based and silicon-based active material layers can be used, and most preferably, a negative electrode active material layer containing the negative electrode composition according to the present application is coated on both sides.
[0173] In one exemplary embodiment of this application, the negative electrode for a lithium secondary battery can be formed by applying a negative electrode slurry containing the negative electrode composition to one or both surfaces of the negative electrode current collector layer and drying the negative electrode slurry.
[0174] In this case, the negative electrode slurry may comprise: the aforementioned negative electrode composition; and a slurry solvent.
[0175] In one exemplary embodiment of this application, the solid content of the negative electrode slurry can be between 5% by weight and 40% by weight.
[0176] In another exemplary embodiment, the solid content of the negative electrode slurry can be in the range of 5% by weight or more and 40% by weight or less, preferably 7% by weight or more and 35% by weight or less, and more preferably 10% by weight or more and 30% by weight or less.
[0177] The solid content of the negative electrode slurry can refer to the content of the negative electrode composition contained in the negative electrode slurry, and can refer to the content of the negative electrode composition relative to 100 parts by weight of the negative electrode slurry.
[0178] When the solid content of the negative electrode slurry meets the above range, the viscosity is suitable during the formation of the active material layer, so the present invention has the feature of being able to effectively form a negative electrode active material layer by minimizing the particle aggregation phenomenon of the negative electrode composition.
[0179] In one exemplary embodiment of this application, the slurry solvent can be used without limitation, as long as the slurry solvent can dissolve the negative electrode composition, but specifically, water or NMP can be used.
[0180] In one exemplary embodiment of this application, the thickness of the negative electrode current collector layer is typically from 1 μm to 100 μm. There are no particular limitations on the negative electrode current collector layer, as long as it has high conductivity and does not cause chemical changes to the battery. For example, materials such as copper, stainless steel, aluminum, nickel, titanium, sintered carbon, copper or stainless steel with surface treatments such as carbon, nickel, titanium, or silver, and aluminum-cadmium alloys can be used. Furthermore, the negative electrode current collector layer can also increase the bonding strength of the negative electrode active material by forming fine irregularities on its surface, and the negative electrode current collector can be used in various forms such as films, sheets, foils, meshes, porous bodies, foams, and nonwoven fabrics.
[0181] In one exemplary embodiment of this application, a negative electrode for a lithium secondary battery is provided, wherein the thickness of the negative electrode current collector layer is 1 μm or more and 100 μm or less, and the thickness of the negative electrode active material layer is 20 μm or more and 500 μm or less.
[0182] However, the thickness can be modified in various ways depending on the type and purpose of the negative electrode used, and is not limited thereto.
[0183] In one exemplary embodiment of this application, the porosity of the negative electrode active material layer can be in the range of 10% or more and 60% or less.
[0184] In another exemplary embodiment, the porosity of the negative electrode active material layer can be in the range of 10% or more and 60% or less, preferably 20% or more and 50% or less, and more preferably 30% or more and 45% or less.
[0185] The porosity varies depending on the composition and content of the silicon-containing active material, conductive material, and binder contained in the negative electrode active material layer. In particular, because the silicon-containing active material and conductive material according to this application are contained in a specific composition and content, satisfying the above range, the conductivity and resistance in the electrode are characterized by having a suitable range.
[0186] In one exemplary embodiment of this application, a lithium secondary battery is provided, comprising: a positive electrode; a negative electrode for a lithium secondary battery according to this application; a separator disposed between the positive electrode and the negative electrode; and an electrolyte.
[0187] Figure 3This is a view illustrating the stacked structure of a lithium secondary battery according to an exemplary embodiment of this application. Specifically, it can be seen that the negative electrode 100 for the lithium secondary battery includes a negative electrode active material layer 20 on one surface (optionally two surfaces) of the negative electrode current collector layer 10, and it can be seen that the positive electrode 200 for the lithium secondary battery includes a positive electrode active material layer 40 on one surface (optionally two surfaces) of the positive electrode current collector layer 50, and it is shown that the negative electrode 100 and the positive electrode 200 for the lithium secondary battery are formed in a structure in which the electrodes are stacked and a separator 30 is interposed therebetween.
[0188] A secondary battery according to an exemplary embodiment of this specification may specifically include the aforementioned negative electrode for a lithium secondary battery. Specifically, the secondary battery may include a negative electrode, a positive electrode, a separator inserted between the positive and negative electrodes, and an electrolyte, and the negative electrode is the same as described above. Since the negative electrode has already been described in detail, its specific description will be omitted.
[0189] The positive electrode may include a positive electrode current collector and a positive electrode active material layer formed on the positive electrode current collector and containing the positive electrode active material.
[0190] In the positive electrode, there are no particular limitations on the positive electrode current collector, as long as it is conductive and does not cause chemical changes to the battery. For example, stainless steel, aluminum, nickel, titanium, sintered carbon, or materials where the surface of aluminum or stainless steel has been surface-treated with carbon, nickel, titanium, silver, etc., can be used. Furthermore, the thickness of the positive electrode current collector can typically be from 3 μm to 500 μm, and the adhesion of the positive electrode active material can be enhanced by forming fine irregularities on the surface of the current collector. For example, the positive electrode current collector can be used in various forms such as films, sheets, foils, meshes, porous bodies, foams, and nonwoven fabrics.
[0191] The positive electrode active material can be a commonly used positive electrode active material. Specifically, the positive electrode active material includes: layered compounds such as lithium cobalt oxide (LiCoO2) and lithium nickel oxide (LiNiO2) or compounds replaced by one or more transition metals; lithium iron oxide such as LiFe3O4; lithium manganese oxide such as Li 1+c1 Mn 2-c1 O4 (0≤c1≤0.33), LiMnO3, LiMn2O3 and LiMnO2; lithium copper oxide (Li2CuO2); vanadium oxides such as LiV3O8, V2O5 and Cu2V2O7; such as LiNi 1-c2 M c2O2 (where M is selected from at least one of the following: Co, Mn, Al, Cu, Fe, Mg, B, and Ga, and c2 satisfies 0.01 ≤ c2 ≤ 0.3) represents a Ni-site type lithium nickel oxide; such as the chemical formula LiMn 2-c3 M c3 Lithium-manganese composite oxides represented by O2 (here, M is selected from at least one of the following: Co, Ni, Fe, Cr, Zn and Ta, and c3 satisfies 0.01≤c3≤0.1) or Li2Mn3MO8 (here, M is selected from at least one of the following: Fe, Co, Ni, Cu and Zn); LiMn2O4, etc., in which Li in the chemical formula is partially replaced by alkaline earth metal ions, but not limited thereto. The cathode may be Li metal.
[0192] Based on the above-mentioned positive electrode active material, the positive electrode active material layer may also include a positive electrode conductive material and a positive electrode binder.
[0193] In this context, the positive electrode conductive material is used to impart conductivity to the electrode and can be used without particular restriction, provided that the positive electrode conductive material is electronically conductive and does not cause chemical changes in the constructed battery. Specific examples include: graphite such as natural or artificial graphite; carbon-containing materials such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal cracking black, and carbon fibers; metal powders or metal fibers such as copper, nickel, aluminum, and silver; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; or conductive polymers such as polyphenylene derivatives, and any one or a mixture of two or more thereof can be used.
[0194] The positive electrode adhesive is used to improve the bonding between positive electrode active material particles and the adhesion between the positive electrode active material and the positive electrode current collector. Specific examples may include polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer (EPDM), sulfonated EPDM, styrene-butadiene rubber (SBR), fluororubber, or various copolymers thereof, and any one or a mixture of two or more thereof may be used.
[0195] The separator separates the negative electrode and the positive electrode and provides a pathway for lithium ion movement. It can be used without particular limitation, as long as it is typically used in lithium secondary batteries. In particular, separators with excellent electrolyte retention and low resistance to ion movement are preferred. Specifically, porous polymer membranes can be used, such as porous polymer membranes formed from polyolefin polymers like ethylene homopolymers, propylene homopolymers, ethylene / butene copolymers, ethylene / hexene copolymers, and ethylene / methacrylate copolymers, or laminates of two or more layers thereof. Alternatively, typical porous nonwoven fabrics can be used, such as nonwoven fabrics made from high-melting-point glass fibers, polyethylene terephthalate fibers, etc. Furthermore, coated separators containing ceramic components or polymeric materials can be used to ensure heat resistance or mechanical strength, and can be selectively used as single-layer or multi-layer structures.
[0196] Examples of the electrolytes include, but are not limited to, organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel polymer electrolytes, solid inorganic electrolytes, and molten inorganic electrolytes that can be used to prepare lithium secondary batteries.
[0197] Specifically, the electrolyte may contain a non-aqueous organic solvent and a metal salt.
[0198] As the non-aqueous organic solvent, for example, aprotic organic solvents such as N-methyl-2-pyrrolidone, propylene carbonate, ethylene carbonate, butyl carbonate, dimethyl carbonate, diethyl carbonate, γ-butyrolactone, 1,2-dimethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolane, formamide, dimethylformamide, dioxolane, acetonitrile, nitromethane, methyl formate, methyl acetate, triphosphate, trimethoxymethane, dioxolane derivatives, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolium ketone, propylene carbonate derivatives, tetrahydrofuran derivatives, ethers, methyl propionate, and ethyl propionate can be used.
[0199] In particular, among the carbonate-based organic solvents, ethylene carbonate and propylene carbonate, as cyclic carbonates, have high dielectric constants as high-viscosity organic solvents, thus effectively dissociating lithium salts, and are therefore preferred for use. Furthermore, when the cyclic carbonates are mixed with low-viscosity and low-dielectric-constant linear carbonates such as dimethyl carbonate and diethyl carbonate in an appropriate ratio, electrolytes with high conductivity can be prepared, and such a combination is even more preferred.
[0200] As the metal salt, a lithium salt can be used, which is a material readily soluble in the non-aqueous electrolyte. For example, as the anion of the lithium salt, one or more selected from the following can be used: F - Cl- I - NO3 - N(CN)2 - BF4 - ClO4 - PF6 - (CF3)2PF4 - (CF3)3PF3 - (CF3)4PF2 - (CF3)5PF - (CF3)6P - CF3SO3 - CF3CF2SO3 - (CF3SO2)2N - (FSO2)2N - CF3CF2(CF3)2CO - (CF3SO2)2CH - (SF5)3C - (CF3SO2)3C - CF3(CF2)7SO3 - CF3CO2 - CH3CO2 - SCN - and (CF3CF2SO2)2N - .
[0201] In the electrolyte, in order to improve battery life characteristics, suppress battery capacity reduction, and improve battery discharge capacity, in addition to the electrolyte components mentioned above, one or more additives such as those listed below may be further included: alkyl carbonate halide esters such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ethers, ethylenediamine, n-glycol dimethyl ether, hexamethylphosphoryltriamine, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted... Zolpidemone, N,N-substituted imidazolidine, ethylene glycol dialkyl ether, ammonium salt, pyrrole, 2-methoxyethanol, or aluminum trichloride.
[0202] An exemplary embodiment of the present invention provides a battery module comprising the secondary battery as a unit cell, and a battery pack comprising the battery module. Because the battery module and the battery pack comprise secondary batteries with high capacity, high rate capability, and good cycle life, they can be used as power sources for medium to large-sized devices selected from electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, and energy storage systems.
[0203] Invention patterns
[0204] Preferred embodiments will be presented below to not only understand the invention, but are provided merely to illustrate the invention, and it will be apparent to those skilled in the art that various substitutions and variations are possible within the scope and spirit of the invention, and such substitutions and variations naturally fall within the scope of the appended claims.
[0205] <Preparation Example>
[0206] <Preparation of negative electrodes in Examples 1-3 and Comparative Examples 1-3>
[0207] <Preparation of the negative electrode>
[0208] A negative electrode slurry (solid concentration of 25% by weight) was prepared by adding silicon-containing active material, first conductive material, second conductive material, and polyacrylamide as a binder in a weight ratio of 80:9.6:0.4:10 to distilled water as a solvent for forming the negative electrode slurry, which meets the particle size and weight ratio in Table 1 below.
[0209] Specifically, the first conductive material is plate-shaped graphite (specific surface area: 17m²). 2 / g, average particle size (D50): 3.5μm), the second conductive material is SWCNT.
[0210] As a specific mixing method, after dispersing the first conductive material, the second conductive material, the binder and water at 2500 rpm for 30 minutes using a homogenizer, the silicon-containing active material is added thereto, and then the resulting mixture is dispersed at 2500 rpm for 30 minutes to prepare a negative electrode slurry.
[0211] The negative electrode slurry was used at 85 mg / 25 cm⁻¹ 2 The loading amount was coated on both surfaces of a copper current collector (thickness: 8 μm) used as the negative electrode current collector. The copper current collector was rolled and dried in a vacuum oven at 130°C for 10 hours to form a negative electrode active material layer (total thickness of the two layers: 33 μm), which was used as the negative electrode (negative electrode thickness: 41 μm, negative electrode porosity 40.0%).
[0212] [Table 1]
[0213]
[0214] In Table 1, Formula 1 can be calculated as (D5 / D50)×100 (%), Formula 2 as (D95 / D50)×100 (%), and Formula 3 as (D5 / D95)×100 (%). Furthermore, in Table 1, the proportion of silicon-containing particles with a particle size of less than 1 μm can be expressed as a weight ratio relative to 100 parts by weight of silicon-containing active material.
[0215] <Example 4>
[0216] The negative electrode was manufactured in the same manner as in Example 1, except that in Example 1, the negative electrode slurry was prepared by adding the silicon-containing active material, the first conductive material, the second conductive material, the third conductive material, and polyacrylamide as a binder to distilled water as a solvent for forming the negative electrode slurry in a weight ratio of 80:5:4.6:0.4:10.
[0217] In this case, the first conductive material in Example 4 is carbon black (specific surface area: 58 m²). 2 / g, diameter: 37nm), the second conductive material in Example 4 is plate-shaped graphite (specific surface area: 17m²). 2 / g, average particle size (D50): 3.5μm), the third conductive material in Example 4 is SWCNT.
[0218] <Example 5>
[0219] The negative electrode was manufactured in the same manner as in Example 1, except that in Example 1, the negative electrode slurry was prepared by adding silicon-containing active material, first conductive material, and polyacrylamide as a binder in a weight ratio of 80:10:10 to distilled water as a solvent for forming the negative electrode slurry.
[0220] In this case, the first conductive material in Example 5 is carbon black (specific surface area: 58 m²). 2 / g, diameter: 37nm).
[0221] <Experimental Example>
[0222] Experimental Example 1: Evaluation of the lifespan of a single battery
[0223] By using LiNi as the positive electrode active material 0.6 Co 0.2 Mn 0.2 O2 (average particle size (D50): 15 μm), carbon black (product name: Super C65, manufacturer: Timcal) as a conductive material, and polyvinylidene fluoride (PVdF) as a binder were added to N-methyl-2-pyrrolidone (NMP) as a solvent for forming the positive electrode slurry in a weight ratio of 97:1.5:1.5 to prepare a positive electrode slurry (solid concentration of 78% by weight).
[0224] The positive electrode slurry was used at 537 mg / 25 cm⁻¹ 2The loading amount is coated on both surfaces of an aluminum current collector (thickness: 12 μm) used as the positive electrode current collector. The aluminum current collector is rolled and dried in a vacuum oven at 130°C for 10 hours to form a positive electrode active material layer (total thickness of the two layers: 65 μm), thereby preparing a positive electrode (positive electrode thickness: 77 μm, porosity: 26%).
[0225] A secondary battery was prepared by inserting a polyethylene separator between the positive electrode prepared above and the negative electrodes of Examples 1 to 5 and Comparative Examples 1 to 3, and injecting an electrolyte therein.
[0226] The electrolyte is obtained by adding 3% by weight of vinylene carbonate relative to the total weight of the electrolyte to an organic solvent in which fluoroethylene carbonate (FEC) and diethyl carbonate (DEC) are mixed in a volume ratio of 30:70, and adding LiPF6 as a lithium salt to the solvent at a concentration of 1M.
[0227] The lifespan and capacity retention of the secondary batteries prepared in Examples 1 to 5 and Comparative Examples 1 to 3 were evaluated using an electrochemical charge-discharge apparatus. The secondary batteries were charged (0.33C CC / CV charge, 4.2V 0.05C cutoff) and discharged (0.33CCC discharge, 3.0V cutoff) using the above charge-discharge cycle as the first cycle. The cycle in which the capacity retention reached 80% from the second cycle onwards was confirmed under the conditions of charging (1.0C CC / CV charge, 4.2V 0.05C cutoff) and discharging (0.5C CC discharge, 3.0V cutoff).
[0228] The capacity retention rate in the Nth cycle is evaluated using the following formula. The results are shown in Table 2 below.
[0229] Capacity retention (%) = {(Discharge capacity in the Nth cycle) / (Discharge capacity in the 1st cycle)} × 100
[0230] Experimental Example 2: Evaluation of the increase in resistance during @SOC50 2.5C discharge (after 300 cycles)
[0231] During the testing of Experiment 1, the capacity retention rate was measured up to 300 cycles. The resistance increase rate was compared and analyzed by discharging the battery at SOC 50 with a 2.5C pulse to measure the resistance. The results are shown in Table 2 below.
[0232] [Table 2]
[0233]
[0234] As can be confirmed in Tables 1 and 2, the lithium secondary battery anode using the silicon-containing active material according to this application is better in terms of service life evaluation and discharge resistance increase rate compared to the lithium secondary battery anodes in Comparative Examples 1 to 3. This is a result of using a silicon-containing active material with controlled micronization of silicon-containing particles, thus satisfying at least the ranges according to Formulas 1 and 2 of this application.
[0235] In other words, it has been confirmed that, since the silicon-containing active materials according to Examples 1 to 5 satisfy the characteristic portion according to this application, fine silicon-containing particles can be removed to form a structure advantageous in terms of curvature within the electrode, thereby preventing an increase in diffusion resistance. Furthermore, even with continuous charge-discharge cycles, the rate of increase in diffusion resistance can be significantly controlled by removing fine silicon particles, thus confirming from Examples 1 to 5 that the lifespan and capacity of the electrode containing the silicon-containing active material are significantly increased.
[0236] Comparative Example 1 corresponds to the case where Formula 1 is not satisfied, Comparative Example 2 corresponds to the case where Formula 2 is not satisfied, and Comparative Example 3 corresponds to the case where both Formula 1 and Formula 2 are not satisfied. In this case, compared with Examples 1 to 5, the pure silicon active material containing uncontrolled micronization of silicon particles shows poor lifespan and discharge resistance increase rate due to side reactions occurring during the charging / discharging process. That is, Comparative Examples 1 to 3 contain fine silicon particles, and it can be confirmed that Comparative Examples 1 to 3 have a structure that is unfavorable in terms of the curvature within the electrode. Furthermore, it can be confirmed that with repeated charging and discharging, the rate of increase in diffusion resistance caused by the SEI layer formed by the reaction between the fine silicon particles and lithium ions increases, thus resulting in poor lifespan and resistance increase rate.
[0237] For reference, Examples 1 to 3 correspond to the case of using planar and linear conductive materials as conductive materials (two conductive materials). In this case, it can be confirmed that the evaluation results of service life are particularly excellent compared to Examples 4 (three conductive materials) and 5 (one conductive material), and the increase rate of discharge resistance is also low. This is because the negative electrode for lithium secondary batteries containing two conductive materials does not significantly affect the service life characteristics of existing lithium secondary batteries. Due to the increased conductive paths, there are many points where the battery can be charged and discharged, thus exhibiting excellent output characteristics at high C-rates.
[0238] Experimental Example 3: R 离子 Evaluation of resistance (measuring orifice resistance using a coin half-cell)
[0239] [Preparation of Symmetrical Cells]
[0240] The negative electrodes prepared in Example 1 and Comparative Example 1 were stamped using a 15-pie stamping press, and coin cells (negative electrode / separator / negative electrode, same electrolyte) were assembled using two electrodes of similar thickness and weight. After the coin cells were fully impregnated with the electrolyte, the pore resistance of the electrodes was measured by measuring the EIS at 100 points with an amplitude of 5 mV from 300 kHz to 100 mHz at room temperature. The results are shown in Table 3 below.
[0241] [Table 3]
[0242] Ohm (Ω) 4.39 7.65
[0243] As can be confirmed in Table 3, by measuring the resistance, it can be confirmed that when the silicon-containing active material according to this application meets the specific ranges of Formulas 1 and 2, a structure advantageous in terms of the curvature within the electrode is formed. Specifically, in order to prevent uneven degradation from the surface portion of the negative electrode into the interior of the negative electrode and to improve the performance of the battery, R 离子 The temperature must be low, and it must be possible to confirm the use of silicon-containing active materials controlled to specific conditions according to this application. 离子 The reduction has been improved.
[0244] In other words, the negative electrode with the silicon-containing active material according to this application has a structure that is advantageous in terms of curvature, and it can be confirmed that the battery diffusion resistance can be improved by improving the conductive path, thereby enhancing the lifespan and durability of the resulting lithium secondary battery.
Claims
1. A negative electrode composition, comprising: a silicon-containing active material; a negative electrode conductive material; and a negative electrode binder, wherein the silicon-containing active material comprises silicon-containing particles having a particle size distribution of 0.01 μm or more and 30 μm or less, relative to 100 parts by weight of the silicon-containing active material, the silicon-containing active material comprises 1 part by weight or more and 5 parts by weight or less of silicon-containing particles having a particle size of 1 μm or less, and the silicon-containing active material satisfies the particle size ratios of the following Formula 1 and Formula 2: [Formula 1] 20 ≤ (X1 / Y) 100(%) [Formula 2] (X2 / Y) 100(%) ≤ 230 In Formula 1 and Formula 2, X1 represents the D5 particle size of the silicon-containing active material, X2 represents the D95 particle size of the silicon-containing active material, and Y represents the median particle size D50 of the silicon-containing active material, wherein D50 is the particle size at the 50% point of the cumulative particle number distribution based on particle size, D95 is the particle size at the 95% point of the cumulative particle number distribution based on particle size, D5 is the particle size at the 5% point of the cumulative particle number distribution based on particle size.
2. The negative electrode composition according to claim 1, wherein the silicon-containing particles comprise one or more selected from SiOₓ where x = 0, SiOₓ where 0 < x < 2, SiC, and Si alloys.
3. The negative electrode composition according to claim 1, wherein the silicon-containing particles comprise one or more selected from SiOₓ where x=0 and SiOₓ where 0<x< 2, and comprise 70 parts by weight or more of the SiOₓ where x=0 relative to 100 parts by weight of the silicon-containing active material.
4. The negative electrode composition according to claim 1, wherein the silicon-containing active material is present in an amount of 60 parts by weight or more relative to 100 parts by weight of the negative electrode composition.
5. The negative electrode composition according to claim 1, wherein the silicon-containing active material satisfies the particle size ratio of the following Formula 3: [Formula 3] 10 ≤ (X1 / X2) 100(%) In Formula 3, X1 represents the D5 particle size of the silicon-containing active material, and X2 represents the D95 particle size of the silicon-containing active material, D95 is the particle size at the 95% point of the cumulative particle number distribution based on particle size, D5 is the particle size at the 5% point of the cumulative particle number distribution based on particle size.
6. The negative electrode composition according to claim 1, wherein the full width at half maximum of the silicon-containing particles having a particle size distribution of 0.01 μm or more and 30 μm or less is 1 μm or more and 5 μm or less.
7. The negative electrode composition according to claim 1, wherein the negative electrode conductive material comprises a planar conductive material and a linear conductive material.
8. The negative electrode composition according to claim 1, wherein 20 ≤ (X1 / Y) 100(%) ≤ 80.
9. The negative electrode composition according to claim 1, wherein 180≤ (X2 / Y) 100(%) ≤ 230。 10. A method for preparing the negative electrode composition according to any one of claims 1 to 9, the method comprising: mixing the negative electrode conductive material and the negative electrode binder to form a mixture; performing first mixing by adding water to the mixture; and performing second mixing by adding the silicon-containing active material to the first-mixed mixture.
11. The method of claim 10, wherein in the first mixing step and the second mixing step, mixing is performed at 2,000 rpm to 3,000 rpm for 10 minutes to 60 minutes.
12. A negative electrode for a lithium secondary battery, comprising: Negative current collector layer; and A negative electrode active material layer is formed on one or both surfaces of the negative electrode current collector layer, the negative electrode active material layer comprising the negative electrode composition according to any one of claims 1 to 9.
13. The negative electrode according to claim 12, wherein the thickness of the negative electrode current collector layer is 1 μm or more and 100 μm or less, and The thickness of the negative electrode active material layer is greater than 20 μm and less than 500 μm.
14. A lithium secondary battery, comprising: positive electrode; The negative electrode for a lithium secondary battery according to claim 12; The membrane between the positive electrode and the negative electrode; and Electrolytes.
Citation Information
Patent Citations
Anode for lithium ion battery
JP2009080971A
Complex cultivation kit using high-temperature ceramic ball topsoil that combines garden and hydroponic complex cultivation and humidification function
KR1020210131869A
Steering knuckles for commercial vehicles, axle assemblies for commercial vehicles and vehicle axles
KR1020220007659A
Silicon oxide, and negative electrode material for lithium ion secondary battery
WO2011033731A1